PENGARUH KUALITAS PELAYANAN PUBLIK DAN DISIPLIN KERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT(Studi Pelayanan Haji Di Kantor Kementerian Agama Kabupaten Kaur): (Studi Pelayanan Haji Di Kantor Kementerian Agama Kabupaten Kaur) - Budiman; Budiman Sakti; Rahimandani; Elza Risanti (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
This research aims to examine the influence of the quality of public services and employee work discipline on public satisfaction in Hajj services at the Ministry of Religion, Kaur Regency. The method used in this research is a sampling method of 50 respondents in the community who will register themselves as prospective pilgrims at the Ministry of Religion of Kaur Regency. There are three problem formulations and hypotheses proposed to be proven through partial tests (t-test) and simultaneous tests (F-test). To analyze the magnitude of each coefficient of public service quality and employee work discipline on the satisfaction of people who receive Hajj services, they are analyzed using a multiple linear regression model. The research results are based on respondents' responses to the indicators used in the research on the variable quality of public services